Lower limb exoskeleton robot and its cooperative control: A review, trends, and challenges for future research - Masengo, Gilbert; Zhang, Xiaodong; Dong, Runlin; Alhassan, Ahmad B.; Hamza, Khaled; Mudaheranwa, Emmanuel (Frontiers in Neurorobotics, 2023)
An effective control of exoskeleton robot (ER) using human-robot interface is crucial for assessing the robot's movements and the force they produce in order to generate effective control signals. Interestingly, certain surveys were done to show off the cutting-edge of exoskeleton robots. The review papers that were previously published have not thoroughly examined the control strategy which is a crucial component of automating the exoskeleton systems. As a result, this review is concentrated on examining the most recent developments and problems associated with the exoskeleton control systems, particularly during the last few years (2017 to 2022). In addition, the trends and challenges of the cooperative control, particularly the multi-information fusion was discussed.